Reasons for foreign listings by South African junior mining and exploration companies - SHAW, VICKI ANN (My University, 2011)
The purpose of the research was to identify the reasons given by South African junior mining and exploration companies for their choice of listing location. This will assist the JSE Securities Exchange in developing a strategy to attract more listings by junior mining and exploration companies. A review of the available literature revealed six possible reasons for the choice of listing location, and these were used as propositions for the remainder of the research. Semi-structured interviews were conducted with CEOs of juniors listed on stock exchanges located in London, Toronto and Johannesburg, mining specialists and Alt-X Designated Advisors. A content analysis was carried out on the data collected. The most significant reason identified in the study is the access to risk capital, followed by the ratings attracted by the company and the liquidity of the exchange. The other reasons identified in the study will depend upon the individual requirements of the companies.
MBA - WBS
Keywords: Mines and mining; Foreign stock exchange listings